The Coupling Effect of Lead and Polishing Treatments on the Passive Films of Alloy 690TT in High-Temperature and High-Pressure Water - Li, Weipeng; He, Jianying; Guo, Liqiu; Li, Jinxu; Qiao, Lijie (Frontiers in Materials, 2019)
In pressurized water reactors, the existence of lead contamination can promote the corrosion of Alloy 690TT. During the manufacturing, transportation, and assembly processes, Alloy 690TT surface is easily scratched and it is easily ignored. The effect of added lead on the scratched surface is different from that on the unscratched surface. In the present study, Alloy 690TT was treated with mechanical polishing (MP) and electrochemical polishing (EP) to generate scratched and unscratched surfaces. With the addition of lead, the thickness of passive film on the MP sample increases by eight times, while that on the EP sample only slightly increases. These chemical composition changes of passive films induced by lead result in the drop of their electrical resistivity, and the electrical resistivity of passive film on the MP sample is reduced by two orders of magnitude, while that on the EP sample decreases only three times. Nevertheless, the thickness and electrical resistivity of passive film on the MP sample are always greater than those of the EP sample. The toxic effect of lead on the MP sample is more severe than that of the EP sample, which may be closely related to their subsurface microstructure. Therefore, Alloy 690TT should better avoid being scratched in the secondary circuit system of pressurized water reactors, as scratched behavior will result in a faster corrosion rate of Alloy 690TT with the presence of lead.